Narrativas docentes sobre gênero no contexto das escolas públicas municipais de Humaitá - AM - Rabelo, Karoline Ribeiro (Brasil, 2021)
This Course Conclusion Paper – TCC, sought to carry out a study on gender issues based on the analysis of practices and teacher training within municipal public schools in Humaitá-AM. Working with the contextualization of the narrative coming from the teachers regarding gender issues as a curricular content and the methodologies used to deal with this theme in the classroom context from the pedagogical practices. We also sought to analyze the curricular policies (BNCC, LDB) present in the classroom. Thus, the main objective is based on identifying gender issues in the context of municipal public schools in Humaitá – AM, based on teachers' narratives about gender identity in their pedagogical practices, as well as analyzing curricular policies about gender and gifts in the classroom. The methodological approach is supported by qualitative research, based on the studies by Rey (2005), where the author states that this methodological approach “[...] represents a permanent process, within which all aspects are constantly defined and redefined. methodological decisions and options during the research process itself” (REY, 2005, p. 81). The instruments for the production of data appropriate the use of interviews, here called resignified narrative interviews, having Andrade (2012) as theoretical-methodological support, as well as the use of document analysis based on Ludke (1986). The discussions on the issue of gender in the school context have shown that the teaching practice must make gender discussions habitual so that such issues become daily, making it possible to speak, question and rethink the social constructions that involve gender identity and resignification of their place in society. The interviews showed that one of the facilitators that mark the entry of these contents into the school environment is the curriculum, which is designed based on the realities of each school and which works in a more flexible way on these issues and integrates new spaces for if we talk, think and rethink about what happens in society and within the school when we deal with gender issues - school - society.